2020
DOI: 10.1016/j.isci.2020.101102
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Induces Lipid Accumulation via 25-Hydroxycholesterol DNA-CpG Methylation

Abstract: This work investigates the relationship between high-glucose (HG) culture, CpG methylation of genes involved in cell signaling pathways, and the regulation of carbohydrate and lipid metabolism in hepatocytes. The results indicate that HG leads to an increase in nuclear 25-hydroxycholesterol (25HC), which specifically activates DNA methyltransferase-1 (DNMT1), and regulates gene expression involved in intracellular lipid metabolism. The results show significant increases in 5m CpG levels in at least 2,225 gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 70 publications
1
41
0
Order By: Relevance
“…25HC plays an important role in lipid accumulation in hepatocytes and development of nonalcoholic fatty liver diseases (NAFLD) [ 42 , 43 ]. 25HC regulates excess acetyl CoA for synthesis of lipids as energy storage.…”
Section: 25-hydroxycholesterol Induces Lipogenesis and Cell Apoptomentioning
confidence: 99%
See 4 more Smart Citations
“…25HC plays an important role in lipid accumulation in hepatocytes and development of nonalcoholic fatty liver diseases (NAFLD) [ 42 , 43 ]. 25HC regulates excess acetyl CoA for synthesis of lipids as energy storage.…”
Section: 25-hydroxycholesterol Induces Lipogenesis and Cell Apoptomentioning
confidence: 99%
“…25HC induces biosynthesis of free fatty acids and triglycerides. Lipid accumulation in hepatocytes induced by high glucose media has been widely used as in vitro model for the study of NAFLD [ 43 , 44 ]. A recent report has shown that, when human hepatocytes were incubated in media containing high glucose levels, 25HC was significantly increased in their nuclei [ 43 ].…”
Section: 25-hydroxycholesterol Induces Lipogenesis and Cell Apoptomentioning
confidence: 99%
See 3 more Smart Citations